Racial Disparities in Patient Activation: The Role of Economic Diversity. (June 2021) - Holt, Jeana M.; Winn, Aaron; Cusatis, Rachel; Talsma, AkkeNeel; Crotty, Bradley H.
The Patient Activation Measure (PAM) assesses a person's level of knowledge, skills, and confidence to self-manage their day-to-day health. We conducted a mediation analysis to examine potential direct effects of race on significantly lower baseline PAM scores in Black than in White participants (p<0.001) who were a subset of 184 adults who participated in a randomized controlled trial. In the mediation analysis, using natural indirect effects, the continuous outcome was the PAM score. The mediators were income, education, ability to pay bills, and health literacy; race (Black or White) was the "exposure." The results indicate that income (p=0.025) and difficulty paying monthly bills (p=0.04) mediated the relationship between race and baseline PAM score, whereas health literacy (p=0.301) and education (p=0.436) did not. Researchers must further investigate the role of economic diversity as an underlying mechanism of patient activation and differences in outcomes. Clinical Trial Registration: Avoiding Health Disparities When Collecting Patient Contextual Data for Clinical Care and Pragmatic Research: NCT03766841 https://clinicaltrials.gov/ct2/show/NCT03766841?term=crotty&draw=2&rank=1